Women's Political and Economic Participation: Implications for the Gender Development Index in Java - Elviana, Elsye; Iskandar, Deden Dinar (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
Inclusive and gender-equitable development is a key objective of Sustainable Development Goal 5 (SDG 5). Despite being the center of Indonesia's economic growth, gender disparities persist across districts and municipalities in Java. This study examines the influence of women's participation in parliament and the labor marker on the Gender Development Index (GDI) in Java during 2017-2023. Women's participation is measured by Women's Parliamentary Representation (KPP) and Women as Professionals (PTP). Maternal Mortality Rate (MMR) and the proportion of women aged 25 and above with at least upper secondary education (PEND) represent health and education dimensions, while Gross Regional Domestic Product (GRDP) serves as a control variable. Using panel data with a Fixed Effect Model, the results show that KPP, PTP, and MMR have no significant effect on GDI, while PEND and GRDP have significant positive effects, highlighting the importance of education and regional economic capacity in supporting gender development.